2016
DOI: 10.3389/fpsyg.2016.00745
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Alpha Oscillations and Pupil Dilation across a Performance-Intensity Function

Abstract: Listening to degraded speech can be challenging and requires a continuous investment of cognitive resources, which is more challenging for those with hearing loss. However, while alpha power (8–12 Hz) and pupil dilation have been suggested as objective correlates of listening effort, it is not clear whether they assess the same cognitive processes involved, or other sensory and/or neurophysiological mechanisms that are associated with the task. Therefore, the aim of this study is to compare alpha power and pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 80 publications
15
73
0
Order By: Relevance
“…This is a region that has been reported to play a crucial role in complex speech comprehension (Van Ettinger-Veenstra et al 2016), especially important in successful comprehension of degraded but predictable speech (Obleser et al 2007;Hartwigsen et al 2015) and importantly in perceptual learning of degraded speech (Eisner et al 2010). The pattern of decreasing alpha power is further consistent with other studies using degradation of complex speech material as for example sentences (McMahon et al 2016;Miles et al 2017). However, studies using short and simple speech stimuli such as single words (Obleser and Weisz 2012;Becker et al 2013) or digits Wöstmann et al 2015) report enhanced alpha for stimuli with more acoustic detail compared to degraded sounds.…”
Section: Alpha Power Decreases Across Degradation Levelssupporting
confidence: 86%
See 2 more Smart Citations
“…This is a region that has been reported to play a crucial role in complex speech comprehension (Van Ettinger-Veenstra et al 2016), especially important in successful comprehension of degraded but predictable speech (Obleser et al 2007;Hartwigsen et al 2015) and importantly in perceptual learning of degraded speech (Eisner et al 2010). The pattern of decreasing alpha power is further consistent with other studies using degradation of complex speech material as for example sentences (McMahon et al 2016;Miles et al 2017). However, studies using short and simple speech stimuli such as single words (Obleser and Weisz 2012;Becker et al 2013) or digits Wöstmann et al 2015) report enhanced alpha for stimuli with more acoustic detail compared to degraded sounds.…”
Section: Alpha Power Decreases Across Degradation Levelssupporting
confidence: 86%
“…Another commonly used measure in studies of degraded speech -a common operationalization for listening effort-is the alpha rhythm (Obleser and Weisz 2012;McMahon et al 2016;Miles et al 2017). Interestingly, we found that alpha power followed a different pattern than coherence which became most obvious in study 2.…”
Section: Alpha Power Decreases Across Degradation Levelsmentioning
confidence: 69%
See 1 more Smart Citation
“…The lateralization of alpha power is indicative of visual-spatial attention (Thut et al, 2012;Wöstmann et al, 2016) and alpha band activity supposedly reflects the selection of sensory information by inhibition (Jensen and Mazaheri, 2010), for example via modulating the excitability of sensory cortices Kayser et al, 2015;Strauss et al, 2015). In auditory perception, the enhancement of alpha activity is often inversely related to signal intelligibility (Becker et al, 2013;McMahon et al, 2016;Obleser and Weisz, 2012;Scharinger et al, 2014;Wostmann et al, 2015), possibly reflecting age-related changes in attentional selection (Gazzaley et al, 2005;Henry et al, 2017;Wostmann et al, 2015). Therefore, it may not be surprising that the relation between alpha activity and perceptual decision making differed between groups.…”
Section: Alpha Activity Cognitive Strategies and Agingmentioning
confidence: 99%
“…In addition, it is evident that studies in this area are relatively recent, since of the 18 selected articles, 72.2% [16][17][18][19][20][21][22][23][24][25][26][27][28] are from the last five years. It should also be noted that the analysis of the articles revealed the lack of national studies that measured the listening effort using physiological indexes as a method of measuring this parameter in both normal hearing individuals and hearing-impaired individuals.…”
Section: Literature Reviewmentioning
confidence: 99%